The influence of 4P marketing on housewives’ spending patterns in Malaysia - Norimah Rambeli, Ramli; Dyg Affizah, Awg Marikan; Noor Al Huda, Abdul Karim; Emilda, Hashim; Asmawi, Hashim (Geografia: International Journal of Development, Society and Environment, 2015)
The main focus of this study is to examine the demographic and psychological factors which influenced the spending patterns of housewives in Malaysia with special emphasis on the role of the 4P (product, price, promotion, place) marketing. Based on the factors, a total of 31 problem statements related to the attitude and the buying decision of housewives were designed. The findings showed that the price factor played an important part in influencing housewives’ spending attitude compared to the factors. By contrast, the location factor (place) was the least important factor in determining the housewives’ spending decision. The study also proved that housewives in Malaysia spent their money according to the household needs. Such attitudinal and decision-making pattern of the housewives means that the government’s regulation of consumer prices should work towards controlling inflation in Malaysia.